PENERAPAN MODEL PROBLEM BASED LERANING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII D SMPN 10 TAPUNG - Frysca Priastiwi; Atma Murni; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absract : This study aims to improve the learning process and improve the student’s mathematical problem solving skill (MPSS) by applying Problem Based Learning (PBL) model. Type of this research is Classroom Action Research with two cycles. This research conducted of class VII D SMPN 10 Tapung on first semester of academic year 2018/2019 wich consists of 32 students. The instruments used in this research were learning instruments and the instruments of collecting data. The learning instruments used include syllabus, lesson plan, and student work sheets. While the instruments of collecting data were observation sheets and MPSS test. Observation sheets were used to find out the data of students and teacher activity during learning process with techniques in this study are descriptive narrative analysis of qualitative data. MPSS test were used to collect the student’s MPSS data which would analyzed quantitatively. After analysis of implementing the PBL model on students and teacher activity, during the learning process student’s participation in learnig more active at each cycles. The MPSS test data of analyzed students’ activity shows an improvement. The mean of the student’s learning achievement for scores early 47,03 increase in cycle I which is 67,14 had improved to 78,13 in cycle II. Improvement of stundent’s learning achievement four each indicator of MPSS identifying for problem, planning problem solving, implement plan to solve the problem, and check results and solusion. This study concludes that the implementation of PBL can improve learning process and student’s MPSS at class VII D SMPN 10 Tapung.Key Words: problem based learning, mathematical problem solving skill, learning process